PROMOTING STUDENTS OF FKIP UNTAN’S POSTS THROUGH BLOG - Dewi, Gina Chandra; Aprialiaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This study aimed at observes whether blog can promote students’ regular B of English study program FKIP Tanjungpura University Pontianak  postings or not. The method of this research is a descriptive research.The data of this research were derived from online observation. There are 26 blog has observed. From the analysis of the data showed students did not really often post their postings on their blogs.(1) 57,69% students always post their postings one or more postings for a year. (2) For genre of text, students did not posted all of genre of text, 50 % students only posted two genre of text, most of students posted report text to promote their postings  (3) 49% students’ postings are students writings. Key words: Promote Postings, Blog, and Descriptive. Abstrak: Penelitian ini bertujuan untuk mengamati apakah blog dapat mempromosikan postingan mahasiswa regular B program studi Bahasa Inggris Universitas Tanjungpura Pontianak atau tidak. Metode dalam penelitian ini adalah penelitian deskriptif. Data diambil menggunakan online observation.Di dalam penelitian ini terdapat 26 blog yang telah di observasi. Dari data yang didapat melalui analisis menunjukan siswa tidak terlalu sering memposting postingan kedalm blog mereka.(1) 57,69% siswa selalu memposting postingan mereka satu atau lebih postingan dalam satu tahun. (2) Untuk jenis teks, siswa tidak memposting semua jenis teks, 50% siswa hanya mempostings dua jenis teks, kebanayakan siswa memposting teks report (3) 49% postingan siswa adalah tulisan mereka.   Kata kunci: Promosi, Postingan, Blog, Deskriptive